Philosophical Foundations of Alternative History in the Perspective of Alexander Demandt - Rogucki, Krzysztof (Sensus Historiae, 2021)
In his book The non-existent history... Alexander Demandt presented a coherent theory of alternative history, in which he defended its scientific value and objective character of the methods used in it. Demandt’s concept is based on the ontology of history: in the open nature of historical processes. This property shows the possibilities of alternative history as well as limitations in the construction of historical alternatives. The German historian’s concept is a permanent contribution to the theory of alternative history.